2006
DOI: 10.1027/1015-5759.22.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure Invariance in the Children's Big Five Questionnaire

Abstract: The factor structure invariance in the Big Five personality questionnaire was studied based on the self-reports of 852 Spanish children. Different degrees of invariance across age groups from 8 to 15 years old, and also according to gender, were investigated by means of confirmatory factor analysis with a matrix of polychoric correlations. The results provide empirical evidence for the invariant factor structure of the Big Five Questionnaire for Children (BFQ-C) measurement across age and gender in children. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 33 publications
1
30
1
3
Order By: Relevance
“…Despite few exceptions (e.g., Block, 2010), there is a general growing consensus that the Big Five dimensions account for cross-culturally valid, coherent, and stable personality self-perceptions not only in adults, but also in children and early adolescents (Barbaranelli, Caprara, Rabasca, & Pastorelli, 2003;Barbaranelli, Fida, Paciello, Giunta, & Caprara, 2008;Caspi & Shiner, 2006;del Barrio, Carrasco, & Holgado, 2006;Measelle, John, Ablow, Cowan, & Cowan, 2005;Tackett et al, 2012). In addition, research has demonstrated the crucial role of the Big Five over many important outcomes, including scholastic achievement (Poropat, 2009) and the development of social relationships (Asendorpf & Denissen, 2006).…”
Section: Personality and Trait Emotional Intelligencementioning
confidence: 97%
“…Despite few exceptions (e.g., Block, 2010), there is a general growing consensus that the Big Five dimensions account for cross-culturally valid, coherent, and stable personality self-perceptions not only in adults, but also in children and early adolescents (Barbaranelli, Caprara, Rabasca, & Pastorelli, 2003;Barbaranelli, Fida, Paciello, Giunta, & Caprara, 2008;Caspi & Shiner, 2006;del Barrio, Carrasco, & Holgado, 2006;Measelle, John, Ablow, Cowan, & Cowan, 2005;Tackett et al, 2012). In addition, research has demonstrated the crucial role of the Big Five over many important outcomes, including scholastic achievement (Poropat, 2009) and the development of social relationships (Asendorpf & Denissen, 2006).…”
Section: Personality and Trait Emotional Intelligencementioning
confidence: 97%
“…Em relação a essa crítica, pode-se argumentar que este é um estudo inicial e que pesquisas futuras deverão utilizar dados provenientes de amostras em diferentes faixas etárias. Apesar disso, Del Barrio et al (2006) Novos estudos são necessários para que se possa aumentar a robustez das evidências encontradas. Apesar das limitações apontadas, este estudo abre o caminho para indagações e novas hipóteses sobre a personalidade humana, buscando contribuir junto à construção do conhecimento no campo dos estudos sobre personalidade.…”
Section: Discussionunclassified
“…The pictorial character of this test takes into account cognitive abilities of young people, in whom, according to Piaget's theory (1974), there takes place the process of thinking development implying the transition of concrete reasoning to abstract reasoning. PBPS-C has its foreign equivalents used, among others, in Italy (Barbaranelli, Caprara, Rabasca, & Pastorelli, 2003), Spain (Del Barrio, Carrasco, & Holgado, 2006), Greece (Kokkinos & Markos, 2015), Germany (Bleidorn & Ostendorf, 2009) and France (Olivier & Herve, 2015). A description of the Polish version can be found in the works of Cieciuch (2010), Maćkiewicz and Cieciuch (2012) and Cieciuch, Toczyłowska-Niemiec, and Barbaranelli (2016).…”
Section: Methodsmentioning
confidence: 99%